2018
DOI: 10.1097/eja.0000000000000804
|View full text |Cite
|
Sign up to set email alerts
|

Protective ventilation during anaesthesia reduces major postoperative complications after lung cancer surgery

Abstract: ClinicalTrials.gov number: NCT00805077.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 36 publications
3
61
0
1
Order By: Relevance
“…As described above, lung protective ventilation not only improved respiratory parameters but also suppressed NLRP3 in ammasome-related in ammatory cytokine secretion and restored the level of endogenous MT: which are likely to be required to improve outcomes during esophageal surgery. Indeed, lung protective ventilation not only reduced the incidence of pulmonary complications but also decreased the rate of major postoperative complications in our study, consistent with the results reported by Marret [29].…”
Section: Discussionsupporting
confidence: 93%
“…As described above, lung protective ventilation not only improved respiratory parameters but also suppressed NLRP3 in ammasome-related in ammatory cytokine secretion and restored the level of endogenous MT: which are likely to be required to improve outcomes during esophageal surgery. Indeed, lung protective ventilation not only reduced the incidence of pulmonary complications but also decreased the rate of major postoperative complications in our study, consistent with the results reported by Marret [29].…”
Section: Discussionsupporting
confidence: 93%
“…Preventing PPCs with specific perioperative ventilatory management is not a new approach [ 16 ]. Many reports have described the concept of protective ventilation [ 17 , 18 ]. Inspired by the results obtained in critical care medicine in patients with acute respiratory distress syndrome (ARDS) [ 19 ], the use of low tidal volumes (6–8 mL/kg predicted body weight) has spread to the operating theater [ 20 22 ] and there is now an established consensus [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial blood gas (ABG) was recorded at T1, T3, T5 (30 min after tracheal extubation) and T6 (the day after the surgery). The lung oxygenation ability was assessed by determining the oxygen index (OI) calculated from the pressure of arterial oxygen (PaO 2 ) and FiO 2 as OI=PaO 2 /FiO 2 (29). Alveolar-arterial differences for oxygen (A-aO 2 ) were calculated from the atmospheric pressure (PB), saturated vapor pressure at room temperature (PH 2 O), pressure of arterial carbon dioxide (PaCO 2 ) and respiration quotient (R), PaO 2 and FiO 2 as A-aO 2 =(PB-PH 2 O) x FiO 2 -PaCO 2 /R-PaO 2 (30), with PB set at 760 mmHg, PH 2 O at 47 mmHg and R at 0.8.…”
Section: Methodsmentioning
confidence: 99%